Oxidative stress parameters in dogs naturally infected with sarcoptic mange - Kerim Emre Yanar; Sefa Kucukler; Emre Eren; Muhammed Sertaç Eroglu; Murat Ilgun; Cihan Gur; Fatih Mehmet Kandemir; Mustafa Sinan Aktas (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: Scabies is one of the most common diseases in dogs. It threatens both animals and humans due to its zoonotic potential. Objective: The purpose of this study was to evaluate the oxidant/antioxidant balance with hematological findings in dogs infested with sarcoptic mange. Methods: The animals evaluated in this study consisted of 32 mixed-breed dogs between 1 and 2 years of age. The dogs were allocated into two groups: a control group (infestation-free animals; n=10), and a sarcoptic mange-infected group (Sarcoptes, n=22). Dogs in the Sarcoptes group showed infestation signs such as intense itching, excoriations, alopecia, and blistering of the elbow and auricular margins. Results: Significant increase (p<0.01) levels were observed in total oxidant status (TOS), malondialdehyde (MDA), oxidative stress index (OSI), and nitric oxide (NO), while glutathione (GSH) and total antioxidant status (TAS) levels in dogs infested with Sarcoptes decreased significantly (p<0.01). In addition, a significant increase (p<0.01) of WBC count in dogs in the sarcoptic group in comparison with the control was found. Conversely, there was significant decrease (p<0.01) in RBC, HGB, and PCV counts in Sarcoptes-infested dogs. Conclusions: Our study suggests a possible relationship between oxidant/antioxidant imbalance and hematological findings in dogs infested with sarcoptic mange. Furthermore, in addition to MDA, TAS, TOS, and OSI markers, NO as well as GSH might be also used to assess the oxidative stress in dogs naturally infected with Sarcoptes scabiei.